Sistema adesivo universal: influência da técnica de condicionamento e da pressão pulpar com soro fetal bovino ou água deionizada na resistência de união à dentina humana - Gonçalves, Lucélia Lemes [UNESP] (2014)
The simulation of pulpal pressure is important for reproduction of in vivo conditions in tests of bond strength. This study evaluated the influence of the etching technique and simulated pulpal pressure with fetal bovine serum or deionized water on bond strength to dentin of Universal Single Bond (3M ESPE;. Brazil Ltda) in vitro. Seventy-two healthy human molars were cut 1 mm below the cemento-enamel junction to separate the crown of radicular portion and cut parallel to the occlusal surface for exposure of 2 mm thickness of dentin. Samples were randomly divided into 3 groups: control group - no pulpal pressure (n = 24); pulpal pressure group serum - pulpal pressure with bovine fetal serum (n = 24); pulpal water pressure group - pulpal pressure with deionized water (n = 24). Then, the subjects were divided into 2 subgroups (n = 12): Subgroup total etch - phosphoric acid 37 % + SB Universal; Self-etch subgroup - SB Universal. The adhesive system was applied according to the technique total-etch or self-etch under pressure simulation with pulp 0 or 15 cm bovine fetal serum or deionized water (throughout the restorative procedure). The specimens were restored with composite resin Filtek Z350 XT (3 m ESPE). After 48 h in deionized water, teeth were sectioned for obtaining beans with 1 mm² adhesive area, and subjected to the test,after 1 day of storage. The variation of bond strength between the groups was analyzed by ANOVA 2-way (simulated pulpal pressure and etch technique) and Tukey (5 % of significance). The highest average bond strength was presented by the group without simulated pulpal pressure self-etch (37.25 ± 4.12) and the lowest average by group simulated pulpal pressure with deionized water and self-etch procedure (26.12 ± 6, 46). There was statistically significant difference for the average bond strength of all groups tested without pressure (36.15a), pulpal ...